Higher Education and Nation-building in the “Newborn” Country of Kosovo - Campbell, Anne; Rexhaj, Qamile Sinanaj; Pozor, Ola (International Higher Education, 2025)
Kosovo, the youngest country in Europe, is often referred to as “newborn.” This paper maps the trajectory of higher education in Kosovo through the lens of internationalization. This article focuses on the ways that higher education internationalization is used as a tool for nation-building, development, and international recognition, highlighting both home-grown initiatives and the influence of foreign donors, as well as ongoing challenges that the “newborn” nation faces to date.